Smaller Foraminifera from Guam. - Todd, Ruth, 1913-1984 (Professional paper (Geological Survey (U.S.)), 1966)
"Four hundred and fifty-three species, subspecies, and varieties (one species new) from upper Eocene, lower Oligocene, Miocene, and Recent deposits."